Attenuation of capsaicin-induced ongoing pain and secondary hyperalgesia during exposure to an immersive virtual reality environment. (November 2019) - Hughes, Sam W.; Zhao, Hongyan; Auvinet, Edouard J.; Strutton, Paul H.
Abstract: Introduction: There is growing evidence that virtual reality (VR) can be used in the treatment of chronic pain conditions. However, further research is required to better understand the analgesic mechanisms during sensitised pain states. Objectives: We examined the effects of an immersive polar VR environment on capsaicin-induced ongoing pain and secondary hyperalgesia. We also investigated whether the degree of analgesia was related to baseline conditioned pain modulation (CPM) responses. Methods: Nineteen subjects had baseline CPM and electrical pain perception (EPP) thresholds measured before the topical application of capsaicin cream. Visual analogue scale ratings were measured to track the development of an ongoing pain state, and EPP thresholds were used to measure secondary hyperalgesia. The effects of a passive polar VR environment on ongoing pain and secondary hyperalgesia were compared with sham VR (ie, 2D monitor screen) in responders to capsaicin (n = 15). Results: Virtual reality was associated with a transient reduction in ongoing pain and an increase in EPP thresholds in an area of secondary hyperalgesia. Baseline CPM measurements showed a significant correlation with VR-induced changes in secondary hyperalgesia, but not with VR-induced changes in ongoing pain perception. There was no correlation between VR-induced changes in pain perception and VR-induced changes in secondary hyperalgesia. Conclusion: Virtual reality can reduce the perception of capsaicin-induced ongoing pain and secondary hyperalgesia. We also show that CPM may provide a means by which to identify individuals likely to respond to VR therapy.